POST-PANDEMIC LEARNING: INTEGRATION OF LOCAL WISDOM AS A LEARNING CONCEPT FOR ELEMENTARY SCHOOL STUDENTS (Adi Widya: Jurnal Pendidikan Dasar, 2023)
This study aims to examine and analyze the value of local wisdom and culture as a learning concept during and after the Covid-19 pandemic. This research is a descriptive study using a qualitative approach. The research was conducted using the literature study method. Data collection was carried out by reviewing references related to the topic under study. The data that has been collected is then analyzed using the data triangulation method. The results of the study show that in order to maximize the quality of learning and the achievement of learning objectives, it is very important to think about transforming and integrating local wisdom and cultural values in learning. This is because local wisdom and culture are a bridge for students, to connect their initial knowledge obtained at home and their environment with academic knowledge obtained at school. Regional cultures that can be used include the philosophy of Tri Hita Karana and Satua Bali. By transforming and integrating local wisdom and cultural values in learning, students are helped to learn meaningfully during and after a pandemic.